Queer adolescent literature as a complement to the english language arts curriculum - Greathouse, Paula; Eisenbach, Brooke; Kaywell, Joan F. (Rowman & Littlefield, 2018)
"This text offers 6th - 12th grade ELA educators guided instructional approaches for including queer-themed young adult (YA) literature in the English language arts classroom. Chapters are authored by leading researchers and theorists in young adult literature, specifically queer-themed YA. Each chapter spotlights the reading of one queer-themed YA novel, and offer pre-, during-, and after reading activities that guide students to a deeper understanding of the content while increasing their literacy practices. While each chapter focuses on a specific queer-themed YA novel, readers will discover the many opportunities for cross-disciplinary study"--Publisher's description.